Development of libyan energy generation model using robust partial least squares-structural equation model (RPLS-SEM) through winsorization - Fadya Ramadan M. Shakim (Tanjong Malim, 2019)
Development of libyan energy generation model using robust partial least squares-structural equation model (RPLS-SEM) through winsorization by Fadya Ramadan M. Shakim